PERANAN LETNAN MASNUR DALAM PERJUANGAN MEMPERTAHKAN KEMERDEKAAN DI BENGKALIS 1945-1950 - ', Elfidayati; ', Isjoni; ', Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Indonesia has achieved independence to be marked with the proclamation on August 17, 1945. The news of independence to the regions in Indonesia with a time that is not simultaneous. After Indonesian independence, the Dutch party wants to dominate Indonesia back and want to erase the sovereignty of Indonesia. From Linggajati negotiations until the Renville negotiations still can not resolve the dispute between Indonesia and the Netherlands. The fighters region also contribute to protecting the territory of the Netherlands who want to launch a military aggression. Including Bengkalis, which was attacked by the Dutch, one of the officers named Lieutenant Masnur withstand the attack of the Dutch military aggression in Bengkalis. The purpose of this study was to determine the life history of Lieutenant Masnur, to find out how the role of Lieutenant Mansur in the struggle for independence in Bengkalis in 1945-1950, to find out how to end the struggle Lieutenant Mansur in the struggle for independence in Bengkalis in 1945-1950. The method used in this research is to use history to step heuristic methodology, interpretation and historiography and data collected through literature, interviews, and documentation and conducted by qualitative. The study site is Bengkalis and Pekanbaru. When the study started from the seminar proposal to the thesis examination. The results showed that Lt. Masnur born in Labuhan booth on October 17, 1927 and then in his youth emigrate to Riau and began his military career to join the fight against the Dutch in Bengkalis. At the end of the struggle Lieutenant masnur back emigrate to Sumatra. Key Words: Struggle, Lieutenant Masnur.